PERAN SEKTOR PERTANIAN DALAM PEREKONOMIAN KABUPATEN INDRAGIRI HILIR PROPINSI RIAU - Sisca Vaulina; Elfi Rahmi (DINAMIKA PERTANIAN, 2013)
The agricultural sector holds an important role in economy of Indragiri Hilir Regency. The objectives of this research were to find out the role of agriculture in the economiy of Indragiri Hilir Regency, to know whether the agricultural sector give a surplus income in economy of Indragiri Hilir Regency, and to analyze subsectors whcich give greatly a multiflier effect on the agricultural sector. The method used case study in Indragiri Hilir Regency with using secondary data of PDRB 2003-2012. The analysis used was Location Quotient (LQ), income surplus and multiplier effect. The results showed that the fisheries subsector, plantation subsector and food crops subsector were subsector basis in economy with LQ value more than 1, while the forestry subsector and livestock subsector had LQ​​ < 1 (non-sector basis). Based on the analysis of surplus income, the plantation subsector provided the greatest surplus income, ranging from Rp.70922.59 to Rp.91586.82. Based on multiplier effect analysis; the food crops subsector gave the greatest multiplier effect. In 2012, this subsector had a multiplier effect of 6.93.